Transcriptome profiling of transcription factors in Ganoderma lucidum in response to methyl jasmonate - Xu, Xiaolan; Zhu, Fengli; Zhu, Yuxuan; Li, Yujie; Zhou, Hao; Chen, Shilin; Ruan, Junshan (Frontiers in Microbiology, 2022)
Ganoderma lucidum is a traditional Chinese medicine and its major active ingredients are ganoderma triterpenoids (GTs). To screen for transcription factors (TFs) that involved in the biosynthetic pathway of GTs in G. lucidum, the chemical composition in mycelia, primordium and fruiting body were analyzed, and the transcriptomes of mycelia induced by methyl jasmonate (MeJA) were analyzed. In addition, the expression level data of MeJA-responsive TFs in mycelia, primordia and fruiting body were downloaded from the database, and the correlation analysis was carried out between their expression profiles and the content of total triterpenoids. The results showed that a total of 89 components were identified, and the content of total triterpenoids was the highest in primordium, followed by fruiting body and mycelia. There were 103 differentially expressed TFs that response to MeJA-induction including 95 upregulated and 8 downregulated genes. These TFs were classified into 22 families including C2H2 (15), TFII-related (12), HTH (9), fungal (8), bZIP (6), HMG (5), DADS (2), etc. Correlation analysis showed that the expression level of GL23559 (MADS), GL26472 (HTH), and GL31187 (HMG) showed a positive correlation with the GTs content, respectively. While the expression level of GL25628 (fungal) and GL26980 (PHD) showed a negative correlation with the GTs content, respectively. Furthermore, the over expression of the Glmhr1 gene (GL25628) in Pichia pastoris GS115 indicated that it might be a negative regulator of GT biosynthesis through decreasing the production of lanosterol. This study provided useful information for a better understanding of the regulation of TFs involved in GT biosynthesis and fungal growth in G. lucidum.